Digital Transformation at Regional General Hospitals of Prof. dr. H.M. Anwar Makkatutu, Bantaeng Regency - Muhajir Muhajir; Haedar Akib; Risma Niswaty (Universitas Kristen Indonesia Toraja, 2022)
Hospitals need adaptation to environmental changes and demands that change rapidly and dynamically. Digital transformation contributes to reducing costs, increasing speed and transparency. The purpose of the research is to describe the implementation, identify the determinants and digital transformation strategies. The method uses a qualitative approach with informants from structural officials, heads of installations, staff, and patients with a total of 15 people. Data were obtained through interviews, observation, and documentation. The results showed that the hospital implemented digital transformation refers to the Generic Process Transformation Model Theory by adding cooperation in the operative stage. The reason for the dominant digital transformation is the need for officers and patients as well as superior services. Impacts include increasing speed, efficiency, transparency, and accountability. The determinant factors include officer competence, teamwork, market strategy, regulation, and cooperation. The dominant inhibiting factors are the comfort zone, sectoral ego, and lack of literacy. According to Albukhitan, there is an update on the digital transformation strategy with the appearance of working together and cultivating innovation.